Analisis Kesalahan Penggunaan Shuushoku Meishi pada Mahasiswa Pendidikan Bahasa Jepang Universitas Negeri Jakarta Angkatan 2024: Analysis of Errors in the Use of Shuushoku Meishi among Japanese Language Education Students at Jakarta State University Class of 2024 - Mochammad Fredy; Nur Saadah Fitri Asih; Poppy Rahayu; Amelya Septiana (Jurnal Pendidikan Bahasa Jepang Undiksha, 2026)
Mastery of shuushoku meishi (modified nouns) is an essential aspect of the Japanese language. This study aims to identify the types and causes of errors in the use of shuushoku meishi made by students of the Japanese Language Education Study Program, class of 2024. The urgency of this research lies in the importance of understanding error patterns to develop more effective learning strategies. A descriptive qualitative approach was employed using error analysis. The data for this study were obtained from students of the Japanese Language Education Study Program at the State University of Jakarta, class of 2024, consisting of written test results regarding the use of shuushoku meishi. Data were collected through a completion test instrument and analyzed using the error analysis method with a descriptive qualitative approach. The findings reveal that 64% of student responses demonstrated an inability to correctly apply shuushoku meishi. The findings reveal that 64% of student responses were incorrect. The types of errors identified include mistakes in constructing shuushoku meishi structures, improper particle usage, errors in character writing (kanji), and inappropriate vocabulary selection. These errors are caused by first-language interference, overgeneralization, weak mastery of Japanese syntax, and a lack of contextual practice. The high error rate indicates a need for enhanced learning strategies that emphasize complex sentence structures and the use of visual media to reinforce comprehension.